Epigenetic Modifications Induced by Nutrients in Early Life Phases: Gender Differences in Metabolic Alteration in Adulthood - Greco, Emanuela A.; Lenzi, Andrea; Migliaccio, Silvia; Gessani, Sandra (Frontiers in Genetics, 2019)
Metabolic chronic diseases, also named non-communicable diseases (NCDs), are considered multifactorial pathologies, which are dramatically increased during the last decades. NCDs such as cardiovascular diseases, obesity, diabetes mellitus, cancers and chronic respiratory diseases dramatically increase morbidity, mortality and socio-economic costs. Moreover, NCDs induce several and complex clinical manifestations that lead to a gradual deterioration of health status and quality of life of affected individuals. Multiple factors can play a role in the development and progression of these diseases such as sedentary behavior, smoking, pollution and unhealthy diet. Indeed, nutrition plays a key role in many aspects of health and dietary imbalances are major determinants of chronic diseases being able to modify metabolic homeostasis. In particular, it appears that specific nutrients and adequate nutrition is important in all period of life, but it is essential during specific times in early life such as pre- and postnatal phases. Indeed, extensive epidemiologic and experimental data show that incorrect nutrition can have health consequences several decades later in life. The hypothesis that epigenetic mechanisms may link such nutritional imbalances with increased disease development has been gaining interest as potential pivotal factor in this last decade. Finally, since endocrine system plays a pivotal role in regulating the metabolism of fats, carbohydrates and proteins throughout life and any hormonal modification of these processes can be expected to lead to an imbalance in metabolism and fat storage, a particular interest to several chemicals able to act as endocrine disruptors has been recently developed. In this review, we will provide an overview and discuss the epigenetic role of some specific nutrients and chemicals in the modulation of physiological and pathological mechanisms.